2003
DOI: 10.1097/01.mlr.0000053230.81725.ef
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy and Declining AIDS Mortality in New York City

Abstract: These results demonstrate that in the case of HAART, the therapeutic benefits of an innovative but costly medical treatment are reaching populations that traditionally have poor access to quality health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 12 publications
2
20
0
1
Order By: Relevance
“…26 Few prior studies in HIV patients have considered differences in clinical outcomes among Hispanic patients compared with other racial/ethnic groups. 4,10,11,13 Of these, 3 reported similar 4,10,13 and 1 reported worse 11 clinical outcomes for Hispanic compared with White patients. Our study is the first to report significantly reduced mortality for HIVinfected Hispanic patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…26 Few prior studies in HIV patients have considered differences in clinical outcomes among Hispanic patients compared with other racial/ethnic groups. 4,10,11,13 Of these, 3 reported similar 4,10,13 and 1 reported worse 11 clinical outcomes for Hispanic compared with White patients. Our study is the first to report significantly reduced mortality for HIVinfected Hispanic patients.…”
Section: Discussionmentioning
confidence: 93%
“…Others have investigated differences in the risk of AIDS or death by race/ethnicity, [4][5][6][7][8][9][10][11][12] but few have included Hispanic patients. 4,10,11,13 Most studies have reported no racial/ethnic differences in clinical progression of HIV, [4][5][6][7][8][9][10]13 although 1 large study indicated that Black and Hispanic patients had higher mortality rates compared with White patients, 11 and another indicated higher mortality rates for Hepatitis C co-infected White compared with Black patients. 12 However, studies were limited by small sample sizes for certain racial/ethnic subgroups, 4,6,9,10,12,13 and limited 7,8,11 or no adjustment 9,12 for potential confounders.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, NYC has long had aggressive public health initiatives to combat major contributors to mortality, with a focus on public policy and prevention efforts among low SES areas of the city. These include intensive tobacco control measures, 16 ongoing aggressive identification and treatment of persons infected with HIV, 17 monitoring and initiating efforts to reduce obesity and diabetes, 18 increased colorectal cancer screening, and outreach to neighborhoods with poor population health indicators through three district public health offices, which conduct activities including delivery of preventive services for hypertension and outreach to limit consumption of sugary drinks. 18 These efforts might have contributed to the continued mortality disparity reductions during 2000-2010.…”
Section: Discussionmentioning
confidence: 99%
“…This study is a longitudinal cohort study of people living with HIV in New York City and is conducted by Columbia University School of Public Health (Messeri, Lee, Abramson, Aidala, Chiasson, and Jessop 2003). The CHAIN cohort was recruited in 1994 from a large number of medical care and social service agencies serving HIV in New York City.…”
Section: A Study Of Hiv-positive People In New York Citymentioning
confidence: 99%
“…These features include: (1) Bayesian regression models to address problems with separation; (2) imputation steps that deal with semi-continuous data; (3) modeling strategies that handle issues of perfect correlation and structural correlation; (4) functions that check the convergence of the imputations; and (5) plotting functions that visually check the imputation models. In Section 4, we demonstrate how to apply these functions using an example of a study of people living with HIV in New York City (Messeri, Lee, Abramson, Aidala, Chiasson, and Jessop 2003). In Section 5, we discuss future plans for our mi package.…”
Section: Introductionmentioning
confidence: 99%